THE INITIAL EVOLUTION OF THE LEXICAL UNIT “ENTREPRENEUR” (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
The study of entrepreneurship covers many disciplines, such as economics, management, sociology and psychology, each of which offers a specific perspective. Economists pay special attention to the role of entrepreneurs in improving economic efficiency, while management professionals study entrepreneurial behavior and leadership. Sociologists study the impact of entrepreneurship on society and demographics, while psychologists study personal characteristics that contribute to entrepreneurial success